2010
DOI: 10.1186/1743-7075-7-38
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium concentration is associated with metabolic factors in the elderly: a cross-sectional study

Abstract: BackgroundSelenium is an essential micronutrient known for its antioxidant function. However, the association of serum selenium with lipid profiles and fasting glucose are inconsistent in populations with average intake of selenium. Furthermore, there were few studies conducted specifically for the elderly. This study examined the relationship of serum selenium concentration with serum lipids and fasting glucose in the Taiwanese elderly population.MethodsThis was a cross-sectional study of 200 males and female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 37 publications
8
31
1
1
Order By: Relevance
“…Kuen-Cheh Yang [32] repoted that serum selenium concentrations were positively associated with serum concentrations of total cholesterol, LDL cholesterol, triglycerides, and glucose this is agreed with this study except glucose, in the two groups serum selenium level was negative associated with glucose level (Table (2) and (3)).…”
Section: ----------------------------------------supporting
confidence: 87%
See 2 more Smart Citations
“…Kuen-Cheh Yang [32] repoted that serum selenium concentrations were positively associated with serum concentrations of total cholesterol, LDL cholesterol, triglycerides, and glucose this is agreed with this study except glucose, in the two groups serum selenium level was negative associated with glucose level (Table (2) and (3)).…”
Section: ----------------------------------------supporting
confidence: 87%
“…Results from studies predicting heart disease using serum levels of selenium [22][23][24][25] have bee inconsistent. Serum selenium levels of diabetic patients were reported to be increased [30][31][32] decreased [33,34] or unchanged [35] compared to controls. Swapnil Rajpathak et al [20] have found that levels of selenium are lower among diabetic men with or without CVD than among healthy controls, In this study, by contrast between two groups of diabetic patient there is significant decrease in selenium level in group II(diabetic patients with CVD) than in group I(diabetic patients).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Similar findings were also reported in a recent cross-sectional study of elderly people from Taiwan. 27 …”
Section: Selenium and Blood Lipidsmentioning
confidence: 99%
“…Although mechanisms for insulin resistance and diabetes are not fully understood, a growing body of evidence suggests that oxidative stress plays an important role in both of their onset and progress [13,14]. While there was a high hope for using antioxidants including Se to prevent and treat diabetes and its complications, a number of recent human trials have actually shown an alarming correlation between high Se intake or body Se status and diabetic risks [15][16][17][18][19][20][21]. Before this revealing, overexpression of GPx1, the "oldest" and most abundant Se-dependent protein, was shown to induce type 2 diabeteslike phenotypes in mice [22][23][24].…”
Section: Introductionmentioning
confidence: 99%